The Effect of the Bio-entrepreneurship-based PJBL Model on Students' Collaborative Problem-Solving Skills - Mira Nurlailatunisa; Rita Fitriani; Dea Diella (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2026)
The demands of 21st-century education require students not only to master conceptual knowledge but also to develop essential skills such as collaboration and problem-solving. These skills are particularly important in biology learning, which often emphasizes real-world applications and teamwork. This study aims to determine the effect of the Bio-entrepreneurship-based Project-Based Learning (PJBL) model on students' collaborative problem-solving (CPS) skills. This study was conducted at a public high school in Tasikmalaya City in the even semester of the 2024/2025 academic year using a quasi-experimental method and a matching-only post-test control group design. The population consisted of 432 tenth-grade students from 12 classes, with samples selected through purposive sampling: class XE-9 as the experimental group and class XE-12 as the control group. Data were collected using an 18-item CPS questionnaire on a 1–4 Likert scale. The results showed that the experimental class achieved a higher mean CPS score (M = 3.01) compared to the control class (M = 2.80). Based on the independent sample t-test, the significance value was 0.043 (p < 0.05), indicating that the Bio-entrepreneurship-based PJBL model had a significant effect on students’ collaborative problem-solving skills in biotechnology learning. These findings imply that integrating entrepreneurial contexts into biology instruction can effectively enhance students’ 21st-century skills, particularly collaborative problem-solving